2010
DOI: 10.1111/j.1476-4431.2010.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Administration of 5% human serum albumin in critically ill small animal patients with hypoalbuminemia: 418 dogs and 170 cats (1994-2008)

Abstract: In this study, administration of 5% HSA appeared to be safe in a large group of critically ill, hypoalbuminemic dogs and cats. The results should be interpreted with caution due to the retrospective, descriptive nature of the study, the absence of control groups and the lack of follow-up data, as well as the potentially life-threatening complications of HSA administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 42 publications
0
54
0
5
Order By: Relevance
“…39 A study performed in 2008 found the use of 25% HSA in critically ill dogs significantly raised serum albumin and total protein concentrations, as well colloid osmotic pressure, particularly in survivors. [40][41][42][43] Therefore although the use of HSA in critically ill dogs appears to be safer than in healthy dogs, caution should be exercised and close monitoring is warranted. [40][41][42][43] Therefore although the use of HSA in critically ill dogs appears to be safer than in healthy dogs, caution should be exercised and close monitoring is warranted.…”
Section: Fluid Challengementioning
confidence: 99%
“…39 A study performed in 2008 found the use of 25% HSA in critically ill dogs significantly raised serum albumin and total protein concentrations, as well colloid osmotic pressure, particularly in survivors. [40][41][42][43] Therefore although the use of HSA in critically ill dogs appears to be safer than in healthy dogs, caution should be exercised and close monitoring is warranted. [40][41][42][43] Therefore although the use of HSA in critically ill dogs appears to be safer than in healthy dogs, caution should be exercised and close monitoring is warranted.…”
Section: Fluid Challengementioning
confidence: 99%
“…Human albumin has been administered to critically ill dogs and cats for numerous disease processes . The administration of HA results in an increase in serum albumin concentration, total plasma protein concentration, systolic blood pressure, and COP .…”
Section: Natural and Synthetic Colloidsmentioning
confidence: 99%
“…The administration of HA results in an increase in serum albumin concentration, total plasma protein concentration, systolic blood pressure, and COP . The administration of HA can result in immediate hypersensitivity reactions that can resolve with discontinuation of product administration . Evaluation of 25% HA administration in healthy dogs revealed that both immediate and delayed hypersensitivity reactions can occur secondary to the development of anti‐HA antibodies .…”
Section: Natural and Synthetic Colloidsmentioning
confidence: 99%
“…Investigation into the use of 25% human serum albumin (HSA) in dogs for the treatment of hypoalbuminemia has been undertaken. Controversy surrounds the use of 25% HSA because adverse reactions including death secondary to administration of 25% HSA have been reported in healthy dogs . Delayed reactions that occur > 48 hours following albumin transfusion have been reported in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…Reported delayed reactions include pulmonary edema, increased respiratory effort, lameness, joint effusions, ecchymoses, renal failure, peripheral edema, lethargy, fever, and cutaneous lesions secondary to vasculitis. Due to the potential for a delayed reaction up to 2 weeks following albumin transfusion, weekly follow up has been recommended …”
Section: Introductionmentioning
confidence: 99%